Geometries, Electronic Structures, and Energetic Parameters of the first-row transition metal doped aluminum clusters Al16M - Trung Kien, Hoang; Tuan Cuong, Ngo; Minh Tam, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 39 No 2DO - 10.25073/2588-1124/vnumap.4775, 2023)
A theoretical study of geometry, stability, electronic structure, and magnetic property of neutral Al 16 M clusters with M being a first-row 3 d transition metal atom, including Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, are investigated in this theoretical study using quantum chemical approaches. The neutral Al 16 M clusters favor three kind of structures based on pure Al 17 framework, including two exohedral doped isomers and one endohedral doped structure. There is a competition between the endoheral and the exohedral structures of Al 16 M with M being Ni, Cu, and Zn. The thermodynamic stability of encapsulated structure Al 16 Ni is confirm by the calculated average binding energy and embedded energy values. DFT calculation, however, indicate that the transition metal doping reduces the ionization potential of the pure aluminum clusters. Based on NBO calculations, a comprehensive picture of magnetic behavior is shown for Al 16 M clusters. Remarkably, the magnetism of the encapsualated Ni dopant is quenched in Al 16 cage. Moreover, NBO calculations found that the 50-electron shells are completely preserved in both clusters Al 16 Sc and Al 16 Ti and the remaining unpaired electron(s) localize(s) mainly on 3 d atomic orbitals of the transition metal dopant.